Improving Third-Grade Students' IPAS Learning Outcomes on Map and Cardinal Directions Through Project-Based Learning Assisted by Wordwall. - Tasya Nur Rochma Habiba; Lailatul Ayu Kurniawati; Aqilah Dieni Haqqi; Agung Setyawan (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2026)
This study aims to overcome low learning outcomes and passive student engagement in Science and Social Studies (IPAS)—specifically regarding maps and compass directions—among 36 third-grade students at UPTD SDN Labang, Bangkalan Regency. To address this issue, the researcher implemented the Project-Based Learning (PjBL) model assisted by interactive Wordwall media. The primary objective is to evaluate the improvement in students' academic achievements after utilizing this engaging teaching method. This Classroom Action Research (CAR) applied Suharsimi Arikunto's methodology across two cycles. Each cycle encompassed four distinct stages: planning, action, observation, and reflection. Data were systematically collected via pre-tests, post-tests, observations, interviews, and documentation, which were then analyzed using quantitative descriptive techniques.The results revealed a consistent and significant improvement in student learning outcomes. The pre-cycle class average was 74.8, which increased to 77.1 in Cycle I, and peaked at 86.1 in Cycle II. The percentage of students achieving academic mastery also rose dramatically. Furthermore, observations indicated that students became highly enthusiastic, actively participating in collaborative group discussions and hands-on project completion. In conclusion, integrating the PjBL model with Wordwall media effectively enhances both cognitive learning outcomes and active student engagement in elementary IPAS education.